Neurons of the Myenteric Plexus of the Rat Ileum Are Vulnerable to the Action of the Herbicide 2,4-Dichlorophenoxyacetic Acid - Germano, Ricardo de Melo; Mari, Renata de Britto; Favetta, Paula Montanhini; Elias, Marcelo Alberto; Trindade, Wesley Alves; Marinsek, Gabriela Pustiglione; Miranda-Neto, Marcílio Hübner de (Journal of Agricultural Studies, 2021)
The herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) is widely used in several countries. Research on the neurotoxicity of 2,4-D has been focused on the central nervous system, and little is known about its effects on the myenteric plexus. Therefore, to elucidate the neurotoxicity of 2,4-D and the viability of its use, we investigated the effects of daily intake of 5 mg 2,4-D/kg for 60 days on the myenteric plexus neurons of the rat ileum using quantitative and morphometric analyses. Twenty male Wistar rats aged 60 days were divided into two groups (n=10 rats/group). The group E animals received daily 5 mg doses of 2,4-D/kg diluted in 1 mL of water, whereas the group C animals were not treated with the herbicide. The animals were euthanized with anesthetic after 60 days; subsequently, the ileum was dissected out, and procedures were performed to visualize the total population of neurons (Giemsa staining), the nitrergic neurons (NADPHd+), and the estimated population of cholinergic neurons (NADPHd-). The results were statistically analyzed and compared between groups. In group E, the densities of Giemsa-stained neurons and NADPHd- neurons decreased (p<0.05) by 7% and 10%, respectively, whereas the density of NADPHd+ neurons remained constant. The cell body area was 5.8% greater (p<0.05) for the NADPHd+ neurons but remained unchanged for the neurons stained with Giemsa. These results suggest that 2,4-D causes a reduction in neuronal density, particularly for cholinergic neurons, and promotes an increase in the cell body area of nitrergic neurons, leading to hypertrophy.